Effects of Positive and Negative Display Polarity on Subjective Visual Fatigue Near Point of Convergence, Among Smartphone Users - Choudhary, Diya; Sunchury, Shrijana; Kour, Sanam Preet; Imtiyaz, Rasheena; sharma, Shivani; Odii, Takhe; Chowdhury, Sweta (International Journal of Aquatic Research and Environmental Studies, 2026)
Increasing smartphone usage has raised concerns about visual health, particularly regarding the effects of screen display polarity on visual fatigue. Positive polarity (dark text on light background) remains the standard mode, while negative polarity (light text on dark background), commonly known as dark mode, has gained popularity due to perceived benefits for eye comfort. However, evidence supporting its effectiveness remains limited and inconsistent, particularly under low ambient lighting conditions. This study investigates the effect of positive and negative polarity display modes on subjective visual fatigue and near point of convergence (NPC) among Android smartphone users in dark room conditions. A descriptive experimental design was employed with 150 healthy participants aged 18–30 years at Sharda University, Greater Noida. Visual acuity and binocular vision were assessed prior to participation. Participants used an Android smartphone in a dark room for 30 minutes in their less-preferred display mode. The NPC was measured before and after the exposure, and a structured questionnaire captured subjective visual fatigue symptoms. Statistical analysis was performed using SPSS version 20, employing Pearson Chi-Square tests. Results indicated that 58% of participants reported eye strain, blurred vision, or discomfort following the exposure. Signs of convergence insufficiency were observed in 40% of participants post-exposure. A statistically significant association was found between display mode and eye strain (χ² = 12.355, p < 0.001), while NPC changes did not significantly differ between modes (χ² = 1.183, p = 0.553). Light mode users demonstrated marginally greater visual fatigue and NPC changes. Both display modalities can impair binocular function and induce visual fatigue, with ambient lighting being a key modulating factor. These findings challenge the assumption that dark mode is universally superior and highlight the need for personalised ergonomic screen settings and regular visual breaks.